KOLABORASI PEMERINTAH, SWASTA DAN MASYARAKAT DALAM PENCEGAHAN STUNTING: STUDI KASUS PROGRAM RUMAH SIGAP (SIAPKAN GENERASI ANAK BERPRESTASI) DI KELURAHAN BANDARHARJO KECAMATAN SEMARANG UTARA - Septiani, Dhuhika Nikmah; Alfirdaus, Laila Kholid; Yuwono, Teguh - (Journal of Politic and Government Studies, 2025)
This study aims to explain collaboration in the stunting prevention program at Rumah SIGAP in Bandarharjo Village, North Semarang District involving the government, private sector, and community. Stunting is a serious health problem that impacts the growth and development of children and the stunting rate in North Semarang District shows a serious number. The theory used is by implementing the Collaborative Governance theory according to Ansel & Gash and the role of collaboration according to Donahue & Zeckhauser. In this context, researcher identified five main indicators of the Collaborative Governance process. They are face-to-face dialogue, building trust, commitment to the process, shared understanding, and intermediate outcomes. In addition, the role of each actor in the collaboration is also described using 4 indicators; productivity collaboration, information collaboration, legitimacy collaboration, and resource collaboration. It was used qualitative approach, with a purposive sampling informant collection technique. The types of data used are primary data from informants directly and secondary data from library references; with data collection techniques in the form of observation, interviews and documentation. The results of the study showed that close collaboration between parties is very important to increase public awareness of nutrition and good parenting. This program has succeeded in reducing stunting rates from 1,416 people at the end of 2022 to 872 people at the end of 2023, and 801 people in October 2024. Although there were some challenges, such as lack of public awareness and economic problems still exist, commitment and regular evaluation from all parties involved are the keys to the success of the program. Thus, it can be seen that effective cross-sector collaboration can have a positive impact on preventing stunting, and is expected to continue to achieve the ultimate goal of zero stunting in the future